Additive Logarithmic Preferences A Further Note - Gorman, W. M. (Review of Economic Studies, 1963)
Journal Article Additive Logarithmic Preferences A Further Note Get access W. M. Gorman W. M. Gorman Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 30, Issue 1, February 1963, Pages 56–62, https://doi.org/10.2307/2296031 Published: 01 February 1963